Verification of Biomedical Processes with Anomalous Diffusion, Transport and Interaction of Species - (:unkn) unknown (Springer Science and Business Media Deutschland GmbH, 2021)
The paper deals with the easily verifiable necessary condition of the preservation of the nonnegativity of the solutions of a system of parabolic equations in the case of the anomalous diffusion with the Laplace operator in a fractional power in one dimension. This necessary condition is vitally important for the applied analysis society because it imposes the necessary form of the system of equations that must be studied mathematically. © 2021, Higher Education Press.
Keywords: Anomalous diffusion; Nonnegativity of solutions; Parabolic systems